2005
DOI: 10.1016/j.jcrs.2004.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of topical tranilast on corneal haze after photorefractive keratectomy

Abstract: Topical tranilast could reduce corneal haze by suppressing TGF-beta1 expression in keratocytes after photorefractive keratectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Study results of tranilast on inflammatory mediators of corneal haze after photorefractive keratectomy may encourage similar testing on allergic conjunctivitis. Tranilast significantly suppressed TGF-b1 expression in keratocytes after photorefractive keratectomy [56 ].…”
Section: Dual Action Agent Versus Placebo or Dual Action Agentmentioning
confidence: 88%
“…Study results of tranilast on inflammatory mediators of corneal haze after photorefractive keratectomy may encourage similar testing on allergic conjunctivitis. Tranilast significantly suppressed TGF-b1 expression in keratocytes after photorefractive keratectomy [56 ].…”
Section: Dual Action Agent Versus Placebo or Dual Action Agentmentioning
confidence: 88%
“…Chihara et al [134] reported that the use of topical tranilast after filtering surgery reduced intraocular pressure and fibrosis of filtering blebs. In addition, corneal haze after photorefractive keratectomy was also reduced with tranilast treatment [135], and it suppressed keratocyte proliferation and collagen synthesis in the corneal haze region, after photorefractive keratectomy [136]. Tani et al [137] showed that tranilast in eye drop form significantly inhibited the formation of stromal haze by inhibiting the proliferation of keratocytes, the abnormal accumulation of extracellular matrix, and the synthesis of collagen in the corneal stroma.…”
Section: Ocular Diseasesmentioning
confidence: 99%
“…24,25 However, it also inhibits the secretion of cytokines such as interleukins and transforming growth factor-␤1, cell proliferation, and collagen synthesis in skin fibroblasts. 26 It has thus also been applied clinically to the treatment of skin keloid and hypertrophic scarring, and its ability to target fibroblasts has been investigated in relation to the treatment of eye conditions such as proliferative vitreoretinopathy, 27,28 corneal haze after photorefractive keratectomy, 29 pterygium, 30 fibrosis of filtering blebs, 31 and posterior capsule opacification. 32 In addition, tranilast was found to inhibit the synthesis of chemokines by various cell types, [33][34][35] suggesting that the suppressive effect of tranilast on allergic inflammation might be mediated in part by the inhibition of chemokine or adhesion molecule expression by fibroblasts.…”
mentioning
confidence: 99%